Implants and inflammation - Where is the future? - Karim El Kholy; Thomas Van Dyke (Wolters Kluwer Medknow Publications, 2015)
The demand for dental implants continues to increase. Implants have replaced fixed and removable prosthetics as the gold standard for replacing missing teeth. Despite the success of the majority of dental implants, biological complications in the form of peri-implant inflammation are common and present as a challenge for both patients and clinicians. The pathogenesis of peri-implantitis was found to be similar to periodontitis. Both are initiated by a bacterial biofilm composed of similar micro-organisms. The inflammatory reaction to the established biofilm is responsible for disease progression and most of the resultant tissue destruction. Treatment strategies for peri-implantitis have mainly been focused on the removal of the bacterial etiology. Limited access and implant surface roughness have proven to be tough challenges for decontaminating exposed implant surfaces. The few attempts using host modulating agents have been abandoned due to drug-associated side effects. Recently, new signaling pathways and molecules involved in the natural resolution of inflammation have been discovered. These indigenous proresolving lipid mediator receptor agonists, such as lipoxins, resolvins, and protectins, provide an opportunity to regulate inflammation in chronic inflammatory diseases such as peri-implantitis while avoiding the undesirable side effects of inhibitory pharmacological agents.